TOXICITY OF THE AQUEOUS EXTRACTS FROM THE FRUITING BODY OF GANODERMA SP. BY BRINE LETHALITY TEST OF Artemia salina Leach. - Rumiyati .; Sismindari .; S.M. Widyastuti (Indonesian Journal of Pharmacy, 2002)
The level of toxicity of aqueous extract from Ganoderma sp. fruiting body isolated from different plant media was determined in this experiment using Brine shrimp lethality test (BST) on Artemia salina Leach. The influence of media on the toxicity level of aqueous extract from Ganoderma sp. fruiting body was determined in this experiment. Ganoderma sp. and G. Lucidum were grown on three flamboyant, (Delonix regia Bojer ex Hook Rafin), sengon (Paraserianthes falcataria (L) Nielsen) and coconut(Cocos nucifera Linn.) plant media. The aqueous extracts were prepared from fruiting body using 0.02 M phosphate buffer pH 7.2. The toxicity level of these aqueous extract were then screened using the BST method. The level of the toxicity was determined by LC50. The results indicated that the aqueous extracts of Ganoderma sp. and G. lucidum isolated from flamboyant, sengon and coconut plant media were influenced by plant media. Ganoderma sp. was isolated from flamboyant plant media possesed the highest toxicity (LC50 480 g aqueous extract/ml), then followed by Ganoderma sp. isolated from sengon plant media (LC50 770 g aqueous extract /ml) and coconut (LC50 1040 g aqueous extract /ml). G. lucidum from coconut plant media possesed the highest toxicity (LC50 660 g aqueous extract /ml), followed by G. lucidum were isolated from sengon plant media (LC50 1100 g aqueous extract /ml) and flamboyant (LC50 1970 g aqueous extract /ml). It was suggested that G.lucidum having highest toxicity might produce compounds having antitumor activity.Key words: Ganoderma sp., aqueous extracts, toxicity .